(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper describes the influence of long term (more than 30 years) fertilizer application to nitrogen, phosphorus, potassium, calcium and magnesium leaching through subsurface drainage in small experimental catchment. The effect of crop and cultivation practice on nutrient concentrations in drainage water is analyzed. This paper presents leaching data during 2011-2013 when spring oilseed rape (OSR), spring barley (SB) and perennial grasses (GC) were grown.The research has been carried out at the Research Institute of Agriculture of Latvian University of Agriculture in the long-term subsurface drainage field established in Skrīveri in 1981 under the guidance of professor J. Štikāns. The long-term drainage field was established in the uncultivated gleyic sod-podzolic Hypostagnic Endogleyic Albeluvisol (Hypereutric), stw-ng-AB(he) loam that had not been used in agriculture for 20 years before. The experimental field was established with four rates of mineral fertilizers: without fertilizers, N45P30K45; N90P60K90 N135P90K135 calculated in form of P2O5 and K2O. Since 1994 a seven-year crop rotation has been organized: 1) winter triticale, 2) potatoes, 3) spring wheat, 4) spring oilseed rape, 5) spring barley + perennial grasses (red clover, timothy), 6) perennial grasses, 1st year of using, and 7) perennial grasses 2nd year of using. The total area (1.6 ha) of the experimental field was divided into 16 plots (15x50 m). Each plot was supplied with a seepage tile drain at the depth of 80-100 cm and an inspection well for drain water sampling and measurement of total water amount.The nitrate nitrogen content in subsurface drain water was significantly affected by fertilizer rate and crop species. The concentration of nitrogen in drain water was significantly lower from non-fertilised plots than from other treatments and was considerably lower growing grass without autumn soil tillage than with conventional ploughing. Different fertilizer rates (applying 30, 60 or 90 kg ha-1 of phosphorus and no fertilizer) had no significant effect on phosphorus concentration in drain water. However, concentration of potassium in drain water depended remarkably (p<0.001) on fertilization rate and was lower from non-fertilized plots. Without autumn ploughing and providing vegetation potassium leaching was significantly lower. The use of fertilizers increased the subsurface water concentration of calcium and magnesium considerably.